Macroeconomic risk and growth in the southeast asian countries : insight from Indonesia - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2023)
Emerging markets offer a unique financial setting, contrasting with developed markets: for example, in the significant contribution of small family-owned businesses to the economy, and the considerable social and economic transformations that profoundly affect businesses. In Indonesia, the authors find family firms are more likely to be involved in real earnings management than non-family firms by reducing operating cash flow to report higher income than non-family firms. Further findings demonstrate institutional ownership significantly reduces firm risk in emerging economies. The authors also consider the impact of the Covid-19 pandemic on systemic risk in the frame of a dual banking system where Islamic and conventional banks coexist. ISETE-33A gives fresh insight into financial and economic issues in Indonesia and ASEAN countries, written by authors from diverse backgrounds. This is essential reading for anyone interested in the financial evolution of these fast-moving economies.